Targeting the Ras pathway in pediatric hematologic malignancies - Pikman, Yana (Curr Opin Pediatr, 2020)
PURPOSE: Ras pathway mutations are one of the most common type of alterations in pediatric hematologic malignancies and are frequently associated with adverse outcomes. Despite ongoing efforts to use targeted treatments, there remain no food and drug administration (FDA) approved medications specifically for children with Ras pathway mutated leukemia. This review will summarize the role of Ras pathway mutations in pediatric leukemia, discuss the current state of RAS pathway inhibitors and highlight the most promising agents currently being evaluated in clinical trials. RECENT FINDINGS: Efficacy of RAF and MEK inhibitors has been demonstrated across multiple solid and brain tumors and these are now considered the standard of care for treatment of certain tumor types in adults and children. Clinical trials are now testing these medications for the first time in pediatric hematologic disorders such as acute lymphoblastic leukemia, juvenile myelomonocytic leukemia and histiocytic disorders. Novel inhibitors of the Ras pathway, including direct RAS inhibitors, are now being tested in clinical trials across a spectrum of pediatric and adult malignancies. SUMMARY: Activation of the Ras pathway is a common finding in pediatric hematologic neoplasms. Implementation of precision medicine with a goal of improving outcomes for these patients will require testing of Ras pathway inhibitors in combination with other drugs in the context of current and future clinical trials.